(untitled) (Journal of the College of Basic Education, 2022)
أن التلوث كظاهرة بيئية موجود منذ أن وجد الإنسان على سطح الأرض، منذ ان اورث الله بني ادم ارض كما في قوله تعالى في سورة البقرة  وَإِذْ قَالَ رَبُّكَ لِلْمَلاَئِكَةِ إِنِّي جَاعِلٌ فِي الأَرْضِ خَلِيفَةً قَالُواْ أَتَجْعَلُ فِيهَا مَن يُفْسِدُ فِيهَا وَيَسْفِكُ الدِّمَاء وَنَحْنُ نُسَبِّحُ بِحَمْدِكَ وَنُقَدِّسُ لَكَ He said, “I know what you do not know.” And the Almighty’s saying in Surah Hud, “He brought you forth from the earth and colonized you in it.” And colonization here is reconstruction, which is by building, planting, or planting. Pollution was necessary for human activity in the first place, but it remained limited for centuries and did not reach the extent of the problem until the industry occupied a